Participación ciudadana y su relación con la planificación estratégica en la Municipalidad Provincial de Ucayali Contamana 2024 - Navarro Perez, Littmy (2025)
The research sought to determine the relationship between citizen participation and strategic planning in the Provincial Municipality of Ucayali Contamana, 2024. A basic methodology was used, with a descriptive correlational level and a non-experimental structure. The population was made up of 80 public servants. The results allowed us to conclude that citizen participation was classified, for the most part, as regular (29%), because the municipality only occasionally invites citizens to participate in the formulation of the concerted development plan. At certain times, the city council promotes community initiatives aimed at cultivating harmony among the community. On the other hand, strategic planning also obtained a regular rating (28%). This result is explained by the fact that respondents perceive that the mission and vision of the municipality are only clear and communicated on certain occasions. Similarly, they sometimes consider that municipal policies are clear and promote an efficient work environment. The results showed significant positive relationships between the different dimensions of citizen participation and strategic planning: general citizen participation showed a high and significant coefficient of 0.851 (p = 0.000); associative participation obtained a strong correlation coefficient of 0.745 with statistical significance (p = 0.000); Regarding voter turnout, the high correlation was 0.721 (p = 0.000), also statistically significant; party participation presented a moderate positive correlation of 0.675, significantly lower but statistically relevant (p = 0.000); finally, civic participation also showed a strong correlation coefficient of 0.796 (p = 0.000).